Indoor parking location information through Short Message Service (SMS) / Nurul Hidayu Abdul Aziz - Abdul Aziz, Nurul Hidayu (2010)
Indoor Parking Location Information through Short Message Service (SMS) is developing to help the drivers to find back their vehicle using their mobile phone via text messaging technology. They may forget the parking location of their vehicle or they are not familiar with the car park. The system prototype will provide information about the location of the vehicle at the indoor car park. This objective of the system prototype is to identify the appropriate Short Message Service (SMS) gateway to deliver the location information of the vehicles, to design and develop the indoor parking vehicle location information prototype and to test the indoor parking location information through Short Message Service (SMS).This system prototype is hope will give a lot of benefit to the driver and mobile user in reducing user time to find back their vehicle with low cost of service. This system prototype is limited to the indoor parking lot only. It is because the Global Positioning System (GPS) give inaccuracy information to the user. It is because it suffers for noise due to weather condition, tree cover and other surrounding structure. When a user is request for the location of their vehicle, the system prototype will give response by sending the location, level and wing of the car park. Sequential search algorithm will be use to do searching of the license plate. Hopefully this system prototype will give a lot of benefit to the user.